2005
DOI: 10.1101/lm.87105
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor antagonist infusions into the basolateral and medial amygdala reveal differential contributions to olfactory vs. context fear conditioning and expression

Abstract: The basolateral amygdala's involvement in fear acquisition and expression to visual and auditory stimuli is well known. The involvement of the basolateral and other amygdala areas in fear acquisition and expression to stimuli of other modalities is less certain. We evaluated the contribution of the basolateral and medial amygdala to olfactory and to context fear and fear conditioning by infusing into these areas the NMDA receptor antagonist AP5, the AMPA/kainate receptor antagonist NBQX, or vehicle prior to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
67
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 68 publications
11
67
1
Order By: Relevance
“…Although there are reciprocal connections between the BLA and MeA (Pitkanen et al, 1997), the fact that sensory inputs converge in the BLA but not in the MeA (Jolkkonen et al, 2001;LeDoux, 2000;Shi and Davis, 2001) suggests that, for fear expression, the MeA may function primarily as an output structure that responds to fear-related signals arriving from the BLA. Our previous findings that pretraining infusions of NBQX into the BLA, but not into the MeA, blocked fear learning, whereas pretest infusions into both structures blocked fear expression are consistent with this view (Walker et al, 2005). Given that BLA projection neurons are largely glutamatergic (Smith and Pare, 1994) and that there are few SP-containing neurons in the BLA (Ribeiro-da-Silva and Hokfelt, 2000; Roberts et al, 1982), it is reasonable to assume that neurotransmission between the BLA and the MeA is primarily glutamatergic, and not tachykininergic.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although there are reciprocal connections between the BLA and MeA (Pitkanen et al, 1997), the fact that sensory inputs converge in the BLA but not in the MeA (Jolkkonen et al, 2001;LeDoux, 2000;Shi and Davis, 2001) suggests that, for fear expression, the MeA may function primarily as an output structure that responds to fear-related signals arriving from the BLA. Our previous findings that pretraining infusions of NBQX into the BLA, but not into the MeA, blocked fear learning, whereas pretest infusions into both structures blocked fear expression are consistent with this view (Walker et al, 2005). Given that BLA projection neurons are largely glutamatergic (Smith and Pare, 1994) and that there are few SP-containing neurons in the BLA (Ribeiro-da-Silva and Hokfelt, 2000; Roberts et al, 1982), it is reasonable to assume that neurotransmission between the BLA and the MeA is primarily glutamatergic, and not tachykininergic.…”
Section: Discussionsupporting
confidence: 73%
“…Fear-potentiated startle is mediated by the CeA and its projection to the deep layers of the superior colliculus/deep mesencephalic nucleus (dSC/DpMe) of the rostral midbrain and, subsequently, to the primary startle reflex circuit in the brain stem Hitchcock and Davis, 1991;Meloni and Davis, 1999;Rosen et al, 1991;Frankland and Yeomans, 1995;Zhao and Davis, 2004). In addition, we recently reported that fear-potentiated startle is also blocked by infusion of the AMPA receptor antagonist NBQX into the MeA (Walker et al, 2005). It is unclear how the MeA influences fear-potentiated startle as it does not project directly to the startle reflex circuit, the dSC/DpMe, or the CeA (Canteras et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together these data suggest that after the first pairing, NMDA receptors are no more involved in the processing of the next pairings or in consolidation processes, comforting our previous data showing an increase in glutamate release in BLA for the first pairing but not for the next ones (Hegoburu et al 2009). This observation is in line with previous studies showing that intra amygdala injections of NMDA antagonists carried out post-training (Maren et al 1996;Walker and Davis 2002) or before testing (Rodrigues et al 2001;Walker et al 2005 in odor fear conditioning) have no effect on consolidation and expression of auditory fear conditioning. However, it is well known that the BLA is involved in memory processes occurring during or just after training and at testing (for review, see Fanselow and Gale 2003).…”
supporting
confidence: 81%
“…APV infused into the prefrontal cortex (but not hippocampus) impaired memory of an odor-food reward association when infused in the prefrontal cortex (Tronel and Sara, 2003). APV infused into the basolateral amygdala disrupted learning in taste-potentiated odor-LiCl aversion (Ferry and Di Scala, 2000;Hatfield and Gallagher, 1995) and in odor-footshock fear conditioning (Walker et al, 2005).…”
Section: Discussionmentioning
confidence: 97%